Contesting Western Narratives: A Multimodal Analysis of Al Jazeera’s Terrorism Discourse on the Israel–Palestine Conflict - Syafuddin, Khairul; Mahanani, Prima Ayu Rizqi; Ihsani, A. Fikri Amiruddin (Fakultas Dakwah UIN Saizu Purwokerto, 2026)
The escalating Israeli Palestinian conflict since October 2023 highlights the role of media in shaping public perception. Al Jazeera English utilizes YouTube to disseminate information globally, influencing opinions through a documentary video entitled